The Proportion of Women Who Have a Breast 4 Years after Breast Cancer Surgery: A Population-Based Cohort Study - Mennie, Joanna C.; Mohanna, Pari-Naz; O’Donoghue, Joseph M; Rainsbury, Richard; Cromwell, David A. (PLOS ONE, 2016)
Background There are numerous pathways in breast cancer treatment, many of which enable women to retain a breast after treatment. We evaluated the proportion of women who have a breast, either through conserving surgery (BCS) or reconstruction, at 4-years after diagnosis, and how this varied by patient group. Methods and Findings We identified women with breast cancer who underwent initial BCS or mastectomy in English National Health Service (NHS) hospitals between January 2008 and December 2009 using the Hospital Episode Statistics (HES) database. Women were assigned into one of four patient groups depending on their age at diagnosis and presence of comorbidities. The series of breast cancer procedure (BCS, mastectomy, immediate, or delayed reconstruction) undergone by each women was identified over four years, and the proportion of women with a breast calculated. Variation was examined across patient groups, and English Cancer Networks. Between 2008 and 2009, 60,959 women underwent BCS or mastectomy. The proportion with a breast at 4 years was 79.3%, and 64.0%, in women less than 70 years without, and with comorbidities. Whilst in women aged 70 and over without, and with comorbidities, proportions were 52.6%, and 38.2%, respectively. Comorbidities were associated with lower proportions of BCS, but had little effect on reconstruction rates unlike age. Networks variation of 15% or more was found within each patient group, and Cancer Networks tended to have either a high or low proportion across all four patient groups. However, while 14% of women under 70 years had undergone reconstruction, less than 2% of women aged 70 or more had this treatment option. Conclusion The proportion of women diagnosed with breast cancer who retain a breast at 4 years is strongly associated with age, and presence of comorbidities. There was significant variation between Cancer Networks indicating that women’s experience in England was dependent on their geographical location of treatment.